Hubungan Antara Dukungan Sosial Dengan Kesejahteraan Subjektif Pada Mahasiswa Rantau - Yosepha Hapsari Lembunai; R. Pasifikus Ch. Wijaya; Marleny Purnamasary Panis (Pusat riset dan Inovasi Nasional, 2025)
Students who live away from home often face various challenges in the adaptation process, ranging from separation from family, demands for independence, to adjustment to a new environment. These factors can increase the risk of feelings of loneliness and psychological problems, and potentially reduce their subjective well-being. This study aims to explore the relationship between social support and subjective well-being among students who live away from home, and to analyze the relationship between each aspect of social support and subjective well-being. The method used in this study is a quantitative approach with a correlational design, and the sampling technique applied is accidental sampling. The population of the study was students who lived away from home, with a sample size of 384 participants. The instruments used in this study included the Multidimensional Scale of Perceived Social Support, the Satisfaction With Life Scale, and the Positive Affect Negative Affect Schedule. The results of the analysis showed a significant positive relationship between social support and subjective well-being, with a p value <0.001. In addition, the correlation analysis of the three aspects of social support showed that each aspect had a significant relationship with subjective well-being. These findings indicate that social support is one of the key factors influencing the subjective well-being of students who live away from home. Thus, it is crucial for students to build a strong social support network to improve their well-being during their time away from home. This research provides valuable insights for developing support programs for students living away from home to help them adapt better. Furthermore, support from friends, family, and the surrounding community can help students cope with the stress and challenges they face during their time away from home. This suggests that building positive social relationships is crucial for their mental and emotional well-being.